2011
DOI: 10.1371/journal.pone.0025976
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone Significantly Increases the Effect of Ionizing Radiation to Cause Mitochondrial Apoptosis via JNK Activation in Cancer Cells

Abstract: Backgroundβ-lapachone (β-lap), has been known to cause NQO1-dependnet death in cancer cells and sensitize cancer cells to ionizing radiation (IR). We investigated the mechanisms underlying the radiosensitization caused by β-lap.Methodology/Principal Findingsβ-lap enhanced the effect of IR to cause clonogenic cells in NQO1+-MDA-MB-231 cells but not in NQO1−-MDA-MB-231 cells. β-lap caused apoptosis only in NQO1+ cells and not in NQO1− cells and it markedly increased IR-induced apoptosis only in NQO1+ cells. Comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 57 publications
(60 reference statements)
3
26
0
Order By: Relevance
“…Similar results were obtained in MEFs completely deficient in CypD (Fig. 6F,G The translocation of AIF from the mitochondrial inter-membrane space to the nucleus is thought to be the pivotal event in PARP1-induced necrotic death (Xu et al, 2006;Moubarak et al, 2007;Artus et al, 2010;Chiu et al, 2011;Park et al, 2011). Immunocytochemistry revealed that both b-Lapachone and MNNG induced the nuclear translocation of AIF (Fig.…”
Section: Mpt Is Not Required For B-lapachone and Mnnginduced Necrosissupporting
confidence: 81%
See 2 more Smart Citations
“…Similar results were obtained in MEFs completely deficient in CypD (Fig. 6F,G The translocation of AIF from the mitochondrial inter-membrane space to the nucleus is thought to be the pivotal event in PARP1-induced necrotic death (Xu et al, 2006;Moubarak et al, 2007;Artus et al, 2010;Chiu et al, 2011;Park et al, 2011). Immunocytochemistry revealed that both b-Lapachone and MNNG induced the nuclear translocation of AIF (Fig.…”
Section: Mpt Is Not Required For B-lapachone and Mnnginduced Necrosissupporting
confidence: 81%
“…A more recent study has also implicated RIP1 and JNK as being part of this process (Chiu et al, 2011). Similarly, JNK activation has been reported as being crucial for b-Lapachone-induced cell death (Shiah et al, 1999;Park et al, 2011), although whether RIP1 is also involved in b-Lapachone's effects has never been tested until the present study. Despite this, we were unable to recapitulate these data in 3T3-transformed Ripk1 2/2 MEFs.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Importantly, the majority of reported cellular effects in blap-treated cancer cells are the result of dramatic NAD + /ATP losses and reactive oxygen species (ROS) formation [reviewed in Bentle et al (5)]. Downstream, l-calpain and JNK activation (30,38) in b-lap-exposed NQO1-proficient (NQO1 + ) cancer cells amplify lethality. l-calpain activation results in specific atypical PARP1 and p53 proteolyses (33) that culminate in potent AIF-endonuclease G-mediated DNA fragmentation detected by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) + staining (6,34).…”
Section: Introductionmentioning
confidence: 99%
“…During ER stress, IRE1 can recruit TRAF2 to the plasma membrane, which leads to the activation of the JNK pathway and subsequent cell death via caspase-12 activation [121]. Other studies demonstrated that JNK activation downstream of ER stress leads to Bax activation, MOMP, and activation of caspase 3 [122]. …”
Section: Ionizing Radiation-induced Cell Toxicitiesmentioning
confidence: 99%